Lever's histopathology of the skin : text and atlas on CD-ROM - Elder, David; Elenitsas, Rosalie; Jaworsky, Christine; Johnson, Bernett, Jr.; Ioffreda. Michael; Miller, Jeffrey J.; Miller, O. Fred, III (Philadelphia : Lippincott Williams & Wilkins, 1999)
(Producer) Portable access to the diagnoctic information for skin disease. Contains entire text from Lever's Histopathology of the Skin, 8th ed.; and Synopsis and Atlas of Lever's Histopathology of the Skin.
CD is available at Koleksi Media Perpustakaan HUKM
Credit: David Elder; Christine Jaworsky; Bernett Johnson,Jr.; Michael Ioffreda; Jeffrey J. Miller; O.Fred Miller III
System requirement: Windows; Windows 3.1 or higher; 16MB RAM; 11MB of free hard disk space; 256 colors
System requirement: Macintosh; System 7.5 or higher; 8MB of free hard disk space; 8MB of RAM; 256 colors
Keywords: Skin Disease -- pathology -- CD-ROM; Skin -- pathology -- atlases -- CD-ROM